Effectiveness of Management Development Programmes and its Impact on Job Satisfaction - S. , Chandrashekar; C. , Madhavi (International Journal of Psychosocial Rehabilitation, 2020)
A management development program is an act that provides managerial skill or knowledge that is needed for the present job and for the future career. The present study was performed in a manufacturing unit, focusing on the managerial personnel. The respondents were those who underwent training in the past one year. Their feedback was sought after completion of training about its effectiveness, and their job satisfaction was also measured. The correlation between training effectiveness and job satisfaction was tested. Also, regression was also performed to test the influence level of the independent variable, training effectiveness, on the dependent variable, job satisfaction.